IL-1 beta as mucosal vaccine adjuvant: the specific induction of tissue-resident memory T cells improves the heterosubtypic immunity against influenza A viruses - Lapuente, D.; Bonsmann, M. Storcksdieck Genannt; Maaske, A.; Stab, V.; Heinecke, V.; Watzstedt, K.; Hess, R.; Westendorf, A. M.; Bayer, W.; Ehrhardt, C.; Tenbusch, Matthias (Mucosal Immunology, 2018)
A universal influenza vaccine must provide protection against antigenically divergent influenza viruses either through broadly neutralizing antibodies or cross-reactive T cells. Here, intranasal immunizations with recombinant adenoviral vectors (rAd) encoding hemagglutinin (HA) and nucleoprotein (NP) in combination with rAd-Interleukin-(IL)-1 beta or rAd-IL-18 were evaluated for their efficacy in BALB/c mice. Mucosal delivery of rAd-IL-1 beta enhanced HA-specific antibody responses including strain-specific neutralizing antibodies. Nevertheless, the beneficial effects on the local T cell responses were much more impressive reflected by increased numbers of CD103(+)CD69(+) tissue-resident memory T cells (T-RM). This increased immunogenicity translated into superior protection against infections with homologous and heterologous strains including H1N1, pH1N1, H3N2, and H7N7. Inhibition of the egress of circulating T cells out of the lymph nodes during the heterologous infection had no impact on the degree of protection underscoring the unique potential of T-RM for the local containment of mucosal infections. The local co-expression of IL-1 beta and antigen lead to the activation of critical checkpoints in the formation of T-RM including activation of epithelial cells, expression of chemokines and adhesion molecules, recruitment of lung-derived CD103(+) DCs, and finally local T-RM imprinting. Given the importance of T-RM-mediated protection at mucosal barriers, this study has major implications for vaccine development.
EVALuna2:35271